Fibromuscular Dysplasia Leading to Spontaneous Coronary Artery Dissection with Sudden Cardiac Arrest - Ata Bajwa; Udit Bhatnagar; Amit Sharma; Hani El-Halawany; Randall C. Thompson (Case Reports in Cardiology)
A 30-year-old previously healthy female, who was six-week postpartum, experienced sudden collapse and tonic-clonic seizure. Emergency medicine services arrived at the scene and the patient was found to be in ventricular fibrillation. Advanced cardiovascular life support (ACLS) was initiated with return of spontaneous circulation. Afterwards, her initial EKG showed atrial fibrillation with rapid ventricular rate, ST elevation in leads II, III, and aVF, and ST depression in V2–V4. She was transferred to a tertiary care hospital where emergent angiogram was performed revealing obstruction of blood flow in the proximal and mid right coronary artery (RCA). A hazy and irregularly contoured appearance of the RCA was consistent with diagnosis of fibromuscular dysplasia. Subsequently, intravascular ultrasonogram (IVUS) was performed which confirmed the diagnosis of RCA dissection. Successful revascularization of the RCA was performed using two bare mental stents. After a complicated course in hospital, she was discharged in stable condition and did very well overall.